2004
DOI: 10.1016/j.femsre.2003.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Some like it cold: biocatalysis at low temperatures

Abstract: In the last few years, increased attention has been focused on a class of organisms called psychrophiles. These organisms, hosts of permanently cold habitats, often display metabolic fluxes more or less comparable to those exhibited by mesophilic organisms at moderate temperatures. Psychrophiles have evolved by producing, among other peculiarities, "cold-adapted" enzymes which have the properties to cope with the reduction of chemical reaction rates induced by low temperatures. Thermal compensation in these en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
292
3
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 369 publications
(319 citation statements)
references
References 125 publications
10
292
3
5
Order By: Relevance
“…Many enzymes from psychrophilic organisms show elevated K m levels for substrates and cofactors compared with mesophilic homologs, indicative of reduced affinity (49,50). Moreover, the K m values often increase further with increasing temperature (53). We observed a slight increase in both the K m (BH 4 ) and [S 0.5 ](L-Phe) of CpPAH when the assay temperature was raised from 10 to 25°C (Table 3).…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Many enzymes from psychrophilic organisms show elevated K m levels for substrates and cofactors compared with mesophilic homologs, indicative of reduced affinity (49,50). Moreover, the K m values often increase further with increasing temperature (53). We observed a slight increase in both the K m (BH 4 ) and [S 0.5 ](L-Phe) of CpPAH when the assay temperature was raised from 10 to 25°C (Table 3).…”
Section: Resultsmentioning
confidence: 79%
“…The increasing availability of crystal structures from other psychrophilic organisms, notably bacteria, has further revealed that cold-adapted enzymes often show high flexibility and thermolability compared with their mesophilic and thermophilic counterparts (50,53,79). Most cold-adapted enzymes show a global rather uniform distribution of their flexibility throughout the three-dimensional structure (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reviews summarized the properties of proteins isolated from thermophiles (Jaenicke and Zavodsky, 1990;Jaenicke, 1991;Adams, 1993;Vieille et al, 1996;Jaenicke and Böhm, 1998;Niehaus et al, 1999;Vieille and Zeikus, 2001;Sterner and Liebl, 2001) and psychrophiles Gerday et al 1997;Sanders et al, 2003;Georlette et al 2004;Siddiqui and Cavicchioli, 2006). Comprehensive studies on crystal structures of thermophilic proteins did not reveal unusual conformations specific to the source type (Petukhov et A c c e p t e d m a n u s c r i p t 5 al., 1997; Facchiano et al, 1998;Karshikoff and Ladenstein, 1998;Szilagyi and Zavodszky, 2000;Kumar et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature adaptation of proteins is mostly relevant for the catalytic properties of the enzymes, as they must adapt the rate of the catalyzed reaction to the growth temperature of the organism. Indeed, thermophilicity studies revealed that psychrophiles synthesize cold-adapted enzymes endowed with a specific activity at low temperatures, significantly higher compared to that possessed by the mesophilic counterparts (Georlette et al, 2004;Siddiqui and Cavicchioli, 2006). On the other hand, the specific activity of hyperthermophilic enzymes reaches its optimum only at high temperatures, close to the optimum growth conditions of the source (Vieille et al, 1996;Vieille and Zeikus, 2001).…”
Section: Introductionmentioning
confidence: 99%